A layered behaviour model for electronic information sharing in Iraq intelligence networks - Abbas, Thamer J. (2017)
The weakness of information sharing has appeared clearly with the events of 11th of Sep 2001 that did not prevent the terrorist attacks. Recently, a prevalent relationship between information sharing and intelligence in the context of counter-terrorism. A few studies have been conducted in this domain by Western countries whilst, none studies done with countries which have effected directly with terrorist attacks especially the Middle East. Issues with information sharing in intelligence domain are still significant challenges. Nevertheless, literature showed there is no single model combined with the technology, information sharing and human factors with an empirical gap in this field, to determine what the intelligence need to develop non-failure intelligence product. This study aims to analysis the technology gap that focuses on fully supporting the common requirements of information sharing in Iraqi intelligence through propose an electronic information sharing model adopted based on Layered Behavioral Model. The fourteen factors are employed in five layers included, Policies and Political Constraints as an Environmental Layer, Compatibility, Information Quality, and Common Data Repository as an Organisation Layer, Cost, Expected Benefits, and Expected Risk as an Information Fusion Center Layer, Technology Capability, Top Management Support, and Coordination as a Readiness Layer, and the last factor in Individual Layer are Trust, Information Stewardship, and Information Security. A quantitative method employed to achieve a broader background of the phenomenon under investigation and to address a broader range of attitude and behavioural issues. This method was a statistical approach in testing the proposed research hypotheses for the factors. From the empirical testing point, found that Policies, Compatibility, Common Data Repository, Cost, Expected Benefits, Expected Risk, Technology Capability, Top Management Support, Trust, Information Stewardship, and Information Security had a significant influence on the degree of electronic information sharing. Whereas, Political Constraints, Information Quality, and Coordination had no significant influence on the degree of electronic information sharing. Several contributions of this study are, create a new theoretical model for the electronic information sharing within intelligence domain. Enhances existing literature by expanding upon layers and factors that are affecting in two dimensions are, electronic information sharing and intelligence. Add new vision to develop information fusion center in the context of electronic information sharing. Reduce the gap of the empirical study in intelligence sectors. And provide a formal strategy and creation a series of the guidelines for Iraqi intelligence authorities to govern E-information sharing activities.